(untitled) (Journal of the College of Basic Education, 2024)
The study dealt with the assessment of air pollution in Kirkuk Governorate for the period (2019-2021), where the monthly and annual rates of a group of gases measured in the center of Kirkuk Governorate at (Shoraw Hospital Station), which is located within the geographic coordinates (35°31’27"N - 44°22’50"(, and (Environment Directorate station), which is located within the geographical coordinates (35°27’18"N - 44°22’54"E), as Iraq came second after Russia in the world for the fourth year in a row among the countries that burn the highest natural gas. The year 2019 recorded values higher than the permissible limits for falling dust in the months (January, March, April, December), and in the year 2020 the months ( March, April) only, As for the year 2021, the month of April was recorded only, and all months and the annual rate of sulfur dioxide (SO2) at the Shoraw Hospital station for the two years (2019, 2020) together are within the global and Iraqi environmental determinants, unlike the year 2021 only in the months (November and December). Together, the month of October is within the global parameters only, and as for the Environment Directorate station, all months and the annual average for the period (2019-2021) are higher than the global and Iraqi parameters combined, except for the month of April of 2019, which recorded a value within the global parameters only .All values of nitrogen oxides (NOx) for the year 2021 were higher than the permissible limits, except for the month of October at the Shoraw Hospital station, and the annual rate for the year 2019 for nitrogen dioxide (NO2) at the Environment Directorate station only recorded a value higher than the permissible limits according to Iraqi standards only. As for the values of carbon monoxide (CO), ozone (O3) and nitric oxide (NO) for the year 2021 at the two study stations, they are within the environmentally permissible limits.